Navigating Stigma and Survival: A Phenomenological Study of HIV Risk Among MSM in Palu, Indonesia - Nur Afni; Nurdin Rahman; Muhammad Ryman Napirah; Andi Mascunra Ami (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: In this study, we aimed to explore the multidimensional social determinants influencing HIV vulnerability among men who have sex with men (MSM) within the context of stigma and exclusion in Indonesia. With high HIV prevalence among MSM and persistent social discrimination, our objective was to examine how social, economic, and structural factors contribute to health risks and hinder access to HIV prevention and care services. Methods: This qualitative study involved a phenomenological approach conducted across the urban setting of Palu, Indonesia, over a three-month period. A total of 15 participants were enrolled, and data were collected through in-depth interviews with purposively selected key informants. Results: The primary outcome of the study was the identification of structural and psychosocial barriers that shape HIV vulnerability, including fear of discrimination, familial rejection, and economic precarity. Additionally, digital platform use and inconsistent condom usage emerged as significant behavioral factors. Statistical analyses were not applicable due to the qualitative nature of the study. However, thematic analysis revealed intersecting themes aligned with the social-ecological model and syndemic theory. Conclusion: In conclusion, our study contributes to the understanding of HIV vulnerability among MSM by highlighting the impact of intersecting stigma, poverty, and systemic exclusion. This research provides insights into the need for community-led and culturally responsive interventions. Future studies should address the integration of economic empowerment strategies and digital outreach mechanisms, ultimately advancing knowledge in the field of international public health.